Why am I in School? Relationships Between Adolescents' Goal Orientation, Academic Achievement and Self-Evaluation - Giota, Joanna (Scandinavian Journal of Educational Research, 2006)
The purpose of the present article is to study the interrelations between goal orientations, achievements and well-being in school. For this purpose adolescents' academic self-perceived competence, personal interest in school subjects, and affect in regard to different evaluative situations that take place in school were related to eight different types of goal orientations toward school and learning. The study suggests that depending on the orientation and domain, adolescents perceive their competence either positively or negatively. In particular, negatively or critically oriented pupils show lower academic performance and self-evaluations of competence, lower future expectations of success with respect to most academic school subjects, and higher levels of anxiety when compared to other pupils. In addition, the study supports the assumption that individuals' beliefs about the self are hierarchically organised and involves beliefs about general or global competence as well as beliefs about specific ability.
Keywords: bien-être; compétence; motivation; résultat scolaire; éducation prioritaire